The use of SGLT2 inhibitors and their impact on coronary artery disease: A literature review (Research, Society and Development, 2023)
Introduction: Acute Coronary Syndrome is responsible for more than one million hospital admissions per year. People with Type 2 Diabetes Mellitus have an increased risk factor for developing this syndrome. Sodium glucose type 2 co-transporter (SGLT2) inhibitors, a medication initially developed as a hypoglycemic agent, have shown favorable responses to protect against cardiovascular events in this population. Objective: This review seeks to assess the benefit of using SGLT2 inhibitors in patients with coronary artery disease and its relationship with clinical outcomes (mortality and length of stay). Method: This is a narrative review of the literature, with data collection in the bases: Scielo, and MEDLINE. Complete articles were included, in English, Portuguese and Spanish, published from 2005 onwards. Duplicate works, with straying from the objective, incomplete and in other languages were excluded. A total of 51 studies composed this review. Results and Discussion: SGLT2 inhibitors are a class of hypoglycemic agents that reduce glucose reabsorption in the proximal renal tubes, increasing urinary glucose excretion through an insulin-independent mechanism. These drugs are known to alleviate oxidative stress and endothelial dysfunction, downregulate systemic inflammation and sympathetic activity, stimulate erythropoietin production, improve heart energy, and reduce preload, afterload, and ventricular mass. Although their impact on atherosclerotic outcomes in large studies of cardiovascular outcomes has been minimal, these properties should, in theory, be beneficial for patients with acute coronary syndrome. Conclusion: SGLT2 inhibitors seem promising in the treatment of acute coronary syndrome, and may be able to improve survival and outcomes in this population.